DAMPAK KEBIJAKAN DIKOTOMI ILMU AGAMA DAN SAINS DALAM KELEMBAGAAN PONDOK PESANTREN AL-JIHAD KOTA PONTIANAK - Murni (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study aims to examine in depth the impact of the policy separating religious knowledge and scientific knowledge within the institutional educational system at Al-Jihad Islamic Boarding School in Pontianak City. The phenomenon of the dichotomy of knowledge, which separates religious sciences from general sciences, is still found in a number of Islamic educational institutions, including pesantren. This research employs a qualitative approach with a case study design. Data were collected through field observations, indepth interviews, and documentation studies. The findings reveal that the practice of knowledge dichotomy in the pesantren is reflected in the division of the curriculum, the separation of study schedules between classical Islamic text studies (kitab) and formal lessons, as well as differences in orientation between religious and general education. The impacts are twofold: on the one hand, it strengthens the identity of the pesantren as a religious institution; on the other hand, it limits efforts to integrate religious and scientific knowledge. Therefore, the development of an integrative curriculum model is needed to connect Islamic values with the advancement of contemporary science.